Interpretations of Zoomorphic Images in the Painted Cave at Sarawak, Malaysia - Junior Kimwah (University of Moratuwa, 2024)
The Painted Cave, located within in the Niah Cave Complex is a cave believed to have been inhabited by the Neolithic people. Inside the cave, there are numerous artefacts including boat-shaped coffins, jewelry made of shells, bones, and ceramics. There are also cave paintings drawn on the cave wall using hematite materials mixed with a mixture of plant liquid material. Zoomorphic refers to images of animals. In this cave, there are several animal images, which have not been adequately interpreted or understood. This paper examines these zoomorphic images which are significant to the community. The paper interprets the zoomorphic images found inside the cave by recording them digitally. The research re-produced the images using Adobe Photoshop’s digital software. By analysing the characteristics, this research identifies these images as being of chicken which it argues could have been important at the time. The paper concludes that the images demonstrate the significance of chicken during the Neolithic period as a source of food. Based on the premise that ancient people drew the images on the cave wall when they believed they are important as part of the history the paper argues that ancient society could have started consuming chicken as their source of protein at that time.